The Multiple Myeloma - Keivan Daneshvar; Wolfram Andreas Bosbach; Nando Mertineit; Gerd Nöldge; Frank Mosler (Swiss Journal of Radiology and Nuclear Medicine)
The second most common hematologic malignancy is the clonal proliferation of neoplastic plasma cells within the bone marrow. There is the presence of monoclonal immunoglobulins in the serum and/or urine. This results in anemia, myelosuppression, bone destruction, and clinical consequences of para-proteinemia on kidney function and other organ systems. The disease manifests through the acronym CRAB (hypercalcemia, renal impairment, anemia, and bone lesions). Less frequent manifestations of multiple myeloma are of extramedullary localizations. Myeloma cells can become independent of the bone marrow microenvironment, circulate freely in the blood, and infiltrate organs. This results in a high-risk state characterized by increased proliferation, evasion of apoptosis, and treatment resistance. It can affect any area of tissue. Most commonly it involves the pleura, lymph nodes, chest wall, liver, skin/soft tissue, lungs, CNS, genitourinary system, breast and pancreas. In patients with confirmed multiple myeloma, the diagnosis of extramedullary involvement is typically established by the presence of pathological soft tissue masses using radiological methods such as computed tomography (CT) scan, positron emission tomography/CT (PET/CT), magnetic resonance imaging (MRI), or ultrasound, along with biopsy or physical examination. The molecular mechanisms underlying the development of extramedullary multiple myeloma (EMM) have not been fully defined. Various cytogenetic abnormalities are observed, and some studies have generated genomic sequencing profiles that distinguish EMM from classic multiple myeloma. While plasma cell leukemia (PCL) and central nervous system (CNS) EMM indicate a poor prognosis, outcomes for other manifestations can be highly heterogeneous. Sensitive imaging modalities including PET/CT and MRI (Fig.1) are integral components of diagnosis and response assessment. Patients with extramedullary multiple myeloma (EMM) have a clear survival disadvantage.